The Effect of Prenatal Yoga on Readiness to Facelabour in third Pregnant Women - Novria Hesti; Yulia Arifin; Viki Yusri (International Health Sciences Journal, 2025)
Prenatal Yoga helps mothers become aware and recognize the physical and psychological changes during pregnancy, and creates communication and bonding with the baby and prepares the mother physically and psychologically for childbirth. Practicing yoga in the third trimester is a useful solution as a medium self help which will reduce discomfort during pregnancy, help with the birthing process and even prepare mentally for the early days after giving birth and while raising a child. The purpose of this research is to see the influence Prenatal Yoga for the readiness of pregnant women to face childbirth at PMB Nomreti Ruslan. Research uses pre-experiment (one group pre-test post-test). The sample consisted of 10 respondents using sampling techniques positive sampling. Prenatal yoga intervention was carried out at TPMB Nomreti Ruslan on November 2 - December 10 2024. The research results use tests Wilcoxon Signed Ranks Test we get ρ value = 0.005 with a value of α = 0.05 (ρ<α), which shows the influence of prenatal yoga on the back pain of pregnant women in the third trimester at the Independent Practice Place of Midwife Nomreti Ruslan, Padang City. It is recommended for midwifery services to use prenatal yoga intervention as one of the programs in preparing third trimester pregnant women for childbirth.